The write start with readings : sentences to paragraphs - Checkett, Lawrence (Harlow;Longman, 2006)
The Write Start: Sentences to Paragraphs 3e, offers writing, mechanics and grammar instruction from the start to help students build the core skills necessary for becoming effective writers.â€œYou Need to Knowâ€ boxes at the beginning of each chapter help students learn by offering a preview of the key concepts presented in the chapter. English as a Second Language instruction is embedded throughout the text. The Write Start also encourages students to see themselves as experts who will use writing in their careers by providing workplace exercises in the end-of-chapter â€œWriting Opportunities.â€